2018
DOI: 10.1007/s00402-018-2933-x
|View full text |Cite
|
Sign up to set email alerts
|

Application and measurement properties of EQ-5D to measure quality of life in patients with upper extremity orthopaedic disorders: a systematic literature review

Abstract: For surgical interventions of the upper extremity, EQ-5D was mostly applied to assess QoL as a primary outcome in patients with shoulder disorders. Investigations of the measurement properties were rare, but indicate good reliability and validity as well as moderate responsiveness in patients with upper extremity conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 69 publications
0
32
1
2
Order By: Relevance
“…Therefore, it might be worthwhile to perform similar reviews for other regions to better inform the selection of PBMs for use in different populations. The test-retest reliability of EQ-5D was found to be either 'inconsistent' or 'insufficient' for almost all populations, which is largely inconsistent with past systematic reviews [91,94,96]. The inferior test-retest reliability of EQ-5D revealed in this review could be related to suboptimal quality of evidence, which was attributable to the imperfect study design.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Therefore, it might be worthwhile to perform similar reviews for other regions to better inform the selection of PBMs for use in different populations. The test-retest reliability of EQ-5D was found to be either 'inconsistent' or 'insufficient' for almost all populations, which is largely inconsistent with past systematic reviews [91,94,96]. The inferior test-retest reliability of EQ-5D revealed in this review could be related to suboptimal quality of evidence, which was attributable to the imperfect study design.…”
Section: Discussioncontrasting
confidence: 85%
“…Satisfactory construct validity and responsiveness were also reported in past systematic reviews of EQ-5D in musculoskeletal [91], schizophrenia [92], skin [93], metabolic [94,95], and respiratory diseases [96]. However, the current finding that EQ-5D is valid and responsive for patients with eye and heart diseases is at odds with the finding from a systematic review [95] that was mainly based on evidence from European populations.…”
Section: Discussionmentioning
confidence: 55%
“…The EQ-5D is commonly used and has been widely compared with other instruments and validated in musculoskeletal health-specific contexts. A recent systematic review demonstrated good reliability and validity and moderate responsiveness [3]. Two studies using cohorts of patients being treated for carpal tunnel syndrome found excellent reliability [4], strong validity and minimal bias for age and gender [5].…”
Section: Introductionmentioning
confidence: 99%
“…All of these patient-reported outcome measures have been used extensively in research and clinical environments and have been reliability and validity tested for patients with MSD. 26,27,3035…”
Section: Methodsmentioning
confidence: 99%